Índice fisicoquímico de la calidad de agua para el manejo de lagunas tropicales de inundación - Pérez Castillo, Ana Gabriela (2008)
We propose ICA-L, a wetland physicochemical water quality index (WWQI), to be used as a management tool for seasonal-flooding lagoons in Palo Verde National Park, Guanacaste, Costa Rica. The goal is to preserve their natural role for native plants as well as migrants and local animal species. The index was developed in four steps: parameter selection, assignment of parameter weight, transformation of data to their corresponding sub indices and selection of an appropriate aggregation function. In this process, the following criteria were used as a reference: WQI from the National Sanitation Foundation, WQI for the Des Moines River, Escribano and De Frutos WQI, the international legislation on maximum acceptable concentration for different water quality vari ables, and the authors’ personal criteria. The index includes the following parameters: dissolved oxygen percent saturation, pH, nitrate concentration, total phosphorus concentration, chemical oxygen demand, concentration of suspended solids, electrical conductivity and temperature. The index sets itself to zero if the concentration of some toxic substance exceeds the maximum allowed limit. The adjustment values were based on “weights” defined in the National Sanitation Foundation Water quality Index (ICA-NSF). In this study, the weight of fecal coliforms count was excluded, the values of turbidity and the one for total solids were integrated into one (suspended solids) and a factor of 0.08 was assigned to the conductivity parameter. The sub indices associated to suspended solids were obtained from the quality of Kahler-Royer variation graph; the values for pH and the nitrate concentration from the graphs constructed for ICA-NSF. The percentage of dissolved oxygen saturation, in sites like irrigation channels, was evaluated directly from the quality variation graph constructed for ICA NSF, whereas the same parameter for the flooding lagoons required an adjustment based on the optimal value for similar non contaminated ecosystems. The conductivity was evaluated from adjustments in the qualification functions commented by Escribano & De Frutos. Chemical oxygen demand, total phosphorus and temperature, were qualified based on the functions developed for the ICA-L.